2003
DOI: 10.1182/blood-2002-07-2329
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant P-selectin glycoprotein ligand–1 directly inhibits leukocyte rolling by all 3 selectins in vivo: complete inhibition of rolling is not required for anti-inflammatory effect

Abstract: Selectin-dependent leukocyte rolling is one of the earliest steps of an acute inflammatory response and, as such, contributes to many inflammatory diseases. Although inhibiting leukocyte rolling with selectin antagonists is a strategy that promises far-reaching clinical benefit, the perceived value of this strategy has been limited by studies using inactive, weak, or poorly characterized antagonists. Recombinant P-selectin glycoprotein ligand-1-immunoglobulin (rPSGL-Ig) is a recombinant form of the best-charac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
59
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 78 publications
(63 citation statements)
references
References 48 publications
4
59
0
Order By: Relevance
“…P-selectin is stored in endothelial cells and platelets and is rapidly mobilized to the cell surface upon stimulation. In this way, regulation of P-selectin expression rapidly alters leukocyte-endothelial interactions (6,27,28). Leukocyte rolling is also mediated by constitutively expressed L-selectin on leukocytes and transcriptionregulated E-selectin expression on endothelial cells (29).…”
Section: Discussionmentioning
confidence: 99%
“…P-selectin is stored in endothelial cells and platelets and is rapidly mobilized to the cell surface upon stimulation. In this way, regulation of P-selectin expression rapidly alters leukocyte-endothelial interactions (6,27,28). Leukocyte rolling is also mediated by constitutively expressed L-selectin on leukocytes and transcriptionregulated E-selectin expression on endothelial cells (29).…”
Section: Discussionmentioning
confidence: 99%
“…25 rPSGL-Ig prevented death induced by 500 ng TNF-␣ and RB6-8C5 in 5 of 6 mice if given prior to TNF-␣ and if heparin was also applied (Figure 4). Intravital microscopy experiments revealed that these mice were also protected from microvascular arrest (not shown).…”
Section: A Role For Selectins In Reactions Induced By Tnf-␣/rb6-8c5mentioning
confidence: 95%
“…All inhibitors were applied at doses previously determined to provide maximum blockade of their respective ligands. 9,14,18,19 …”
Section: Reagentsmentioning
confidence: 99%